The trend of BMI values among US adults - John Komlos; Marek Brabec (Center for Economic Studies and ifo Institute (CESifo), 2010)
Background: The trend in the BMI values of the US population has not been estimated accurately because time series data are unavailable and because the focus has been on calculating period effects. Object: To estimate the trend and rate of change of BMI values by birth cohorts stratified by gender and ethnicity born 1882-1986. Methods: We use loess additive regression models to estimate age and trend effects of BMI values of US-born black and white adults measured between 1959 and 2006. We use all the NHES and NHANES survey data. Results: The increase in BMI was already underway among the birth cohorts of the early 20th century. The rate of increase was fastest among black females; for the three other groups under consideration, the rates of increase were similar. The generally persistent upward trend was punctuated by upsurges, particularly after each of the two World Wars. That the estimated rate of change of BMI values increased by 71% among black females between the birth cohorts 1955 and those of 1965 is indicative of the rapid increases in their weight. Conclusion: We inference that transition to post-industrial weights was a gradual process and began considerably earlier than hitherto supposed.
Keywords: I10; N00; 330; BMI; US; NHANES; obesity; overweight; semiparametric modeling; Gesundheit; Gesundheitsrisiko; Geschichte; Industrialisierung; USA